Young Zambian infants with symptomatic RSV and pertussis infections are frequently prescribed inappropriate antibiotics: a retrospective analysis - Christian E. Gunning; Pejman Rohani; Lawrence Mwananyanda; Geoffrey Kwenda; Zacharia Mupila; Christopher J. Gill (PeerJ, 2023)
Pediatric community-acquired pneumonia (CAP) remains a pressing global health concern, particularly in low-resource settings where diagnosis and treatment rely on empiric, symptoms-based guidelines such as the WHO’s Integrated Management of Childhood Illness (IMCI). This study details the delivery of IMCI-based health care to 1,320 young infants and their mothers in a low-resource urban community in Lusaka, Zambia during 2015. Our Southern Africa Mother Infant Pertussis Study (SAMIPS) prospectively monitored a cohort of mother/infant pairs across infants’ first four months of life, recording symptoms of respiratory infection and antibiotics prescriptions (predominantly penicillins), and tested nasopharyngeal (NP) samples for respiratory syncytial virus (RSV) and Bordetella pertussis. Our retrospective analysis of the SAMIPS cohort found that symptoms and antibiotics use were more common in infants (43% and 15.7%) than in mothers (16.6% and 8%), while RSV and B. pertussis were observed at similar rates in infants (2.7% and 32.5%) and mothers (2% and 35.5%), albeit frequently at very low levels. In infants, we observed strong associations between symptoms, pathogen detection, and antibiotics use. Critically, we demonstrate that non-macrolide antibiotics were commonly prescribed for pertussis infections, some of which persisted across many weeks. We speculate that improved diagnostic specificity and/or clinician education paired with timely, appropriate treatment of pertussis could substantially reduce the burden of this disease while reducing the off-target use of penicillins.